Characterization of a sensitive mouse Aβ40 PD biomarker assay for Alzheimer's disease drug development in wild-type mice. (May 2016) - Lu, Yanmei; Hoyte, Kwame; Montgomery, William H; Luk, Wilman; He, Dongping; Meilandt, William J; Zuchero, Y Joy Yu; Atwal, Jasvinder K; Scearce-Levie, Kimberly; Watts, Ryan J; DeForge, Laura E
Aim: Transgenic mice that overexpress human amyloid precursor protein with Swedish or London ( APPswe or APPlon ) mutations have been widely used for preclinical Alzheimer's disease (AD) drug development. AD patients, however, rarely possess these mutations or overexpress APP.Results: We developed a sensitive ELISA that specifically and accurately measures low levels of endogenous Aβ40 in mouse plasma, brain and CSF. In wild-type mice treated with a bispecific anti-TfR/BACE1 antibody, significant Aβ reductions were observed in the periphery and the brain. APPlon transgenic mice showed a slightly less reduction, whereas APPswe mice did not have any decrease.Conclusion: This sensitive and well-characterized mouse Aβ40 assay enables the use of wild-type mice for preclinical PK/PD and efficacy studies of potential AD therapeutics.